2017
DOI: 10.1007/s13346-017-0390-7
|View full text |Cite
|
Sign up to set email alerts
|

Emulsion versus nanoemulsion: how much is the formulative shift critical for a cosmetic product?

Abstract: The use of nanoemulsions in cosmetic products has been enlarged in the last decades because of several formulative advantages (e.g., the improved self-life stability, better texture properties). In addition, nanoemulsions seemed to improve the penetration of active ingredients through the human skin, comparing to conventional emulsion. In this contest, the risk of a higher systemic exposure of consumer to active ingredients, due to the ability of nanoemulsion to enhance permeation, results a critical attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Light scattering on nanoscale colloidal systems causes a characteristic bluish reflection called the Tyndall Effect and represents a parameter indicative of the kinetic stability acquired by nano-emulsions compared to macroemulsions [ 44 ]. However, nano-emulsion are susceptible to flocculation, coalescence and sedimentation instabilities [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Light scattering on nanoscale colloidal systems causes a characteristic bluish reflection called the Tyndall Effect and represents a parameter indicative of the kinetic stability acquired by nano-emulsions compared to macroemulsions [ 44 ]. However, nano-emulsion are susceptible to flocculation, coalescence and sedimentation instabilities [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The human epidermis membrane used for in vitro permeation studies was obtained from the abdominal skin of a single donor. The epidermis was prepared according to the heat separation method, as previously reported [33].…”
Section: Methodsmentioning
confidence: 99%
“…The authors observed comparable permeation in both emulsion and nanoemulsion forms of caffeine. Retention was higher (though not significantly different) in the caffeine emulsion (Musazzi et al 2018). In a separate study, Shakeel and Ramadan observed that caffeine nanoemulsion exhibited a better in vitro skin permeation profile compared with caffeine aqueous solution (Shakeel and Ramadan 2010).…”
Section: Alkaloidsmentioning
confidence: 80%